Deconstruction and Terrorism in Jacques Derrida A study of the events of 11th of Septembre - Shbani , Monzer (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
This research tackled the attitude of deconstruction in general and Jacques Derrid's. the Founder of deconstruction, and the basics out of which they came up with their concepts, phenomena and events. Then, it proceeds to discuss terrorism as a deconstructable concept taking in to account the essential factors lagging behind terrorism as a phenomenon to avoid shallowness, The research managed to tackle in particularly in regards to 11th of September as one sample of a deconstructive attitude towards terrorism in it's linguistic, religious and political fields, all of them seeking an international reform Jacques derrida, on the other hand, is presented here in the study. As more than a mere founder of deconstruction who deconstructs this phenomenon and terrorist speech. Rather we come to perceive Derrida with an attitude particularly towards that of the 11 the of September